The potassium puzzle: exploring the intriguing connection to albuminuria - Yuan, Weihua; Wang, Tiancheng; Yue, Wei (Frontiers in Nutrition, 2024)
Background: Studies have revealed a relationship between dietary potassium intake and albuminuria, despite the fact that the human body needs a lot of potassium. Our study concentrated on the link between dietary potassium intake and albuminuria. Methods: This study used subgroup analysis and weighted multivariate regression analysis. Data from the National Health and Nutrition Examination Survey (NHANES) were examined to determine the urinary albumin-to-creatinine ratio (ACR) and participant age (20 years or older). ACR >30 mg/g was the threshold for albuminuria. Results: 7564 individuals in all were included in the study. The link between the two was significant in both our original model (OR=0.99; 95% CI, 0.98-0.99, p < 0.0001) and the minimum adjusted model (OR=0.99; 95% CI, 0.98-0.99, p < 0.0001). A fully adjusted model did not change the significance of the negative correlation between potassium consumption and albuminuria (OR = 0.99; 95% CI, 0.98-1.00, p = 0.0005), indicating that each unit increase in potassium intake was related with a 1% decrease in the chance of developing albuminuria. The negative correlation between potassium intake and albuminuria was not significantly influenced by sex, age, BMI, hypertension, diabetes, or smoking, according to interaction tests (p for interaction >0.05). Conclusions: Reduced risk of albuminuria was linked to higher dietary potassium intake. The particular mechanism linking the two still has to be explained by several inventive and prospective studies.